Antioxidant, lipase and ACE‐inhibitory properties of camel lactoferrin and its enzymatic hydrolysates. (22nd August 2022) - Oussaief, Olfa; Jrad, Zeineb; Adt, Isabelle; Kaddes, Khaoula; Khorchani, Touhami; Degraeve, Pascal; El Hatmi, Halima
Abstract : The antioxidant and the lipase and the angiotensin‐converting enzyme (ACE) inhibitory properties of camel lactoferrin and its hydrolysates elaborated with four proteolytic enzymes (trypsin, α‐chymotrypsin, pancreatin and papain) were assessed. Lactoferrin was purified from camel colostrum using cation exchange chromatography. Camel lactoferrin hydrolysates showed different degrees of hydrolysis, reverse phase‐HPLC profiles and molecular weight distributions, reflecting heterogeneity in terms of polarity and molecular weight of the generated peptides. Camel lactoferrin hydrolysates exhibited higher antioxidant, lipase and ACE inhibitory activities than native lactoferrin. Pancreatin‐generated hydrolysates showed the highest lipase inhibitory activity (48.1%), while papain‐generated hydrolysates presented the greatest ACE inhibitory activity (89.14%). Abstract : Biological activities of camel lactoferrin and its enzymatic hydrolysates.